A simple inland culture system provides insights into ascidian post-embryonic developmental physiology - Birthe Thuesen Mathiesen; Mayu Ohta; Boris Pinto De Magalhaes; Chiara Castelletti; Vincenzo Perria; Keaton Schuster; Lionel Christiaen; Naoyuki Ohta (Open Biology)
Maintenance and breeding of experimental organisms are fundamental to life sciences, but both initial and running costs, and hands-on zootechnical demands can be challenging for many laboratories. Here, we first aimed to further develop a simple protocol for reliable inland culture of tunicate model species of the Ciona genus. We cultured both Ciona robusta and Ciona intestinalis in controlled experimental conditions, with a focus on dietary variables, and quantified growth and maturation parameters. From statistical analysis of these standardized datasets, we gained insights into the post-embryonic developmental physiology of Ciona and inferred an improved diet and culturing conditions for sexual maturation. We showed that body length is a critical determinant of both somatic and sexual maturation, which suggests the existence of systemic control mechanisms of resource allocation towards somatic growth or maturation and supports applying size selection as a predictor of reproductive fitness in our inland culture to keep the healthiest animals at low density in the system. In the end, we successfully established a new protocol, including size selection, to promote both sperm and egg production. Our protocol using small tanks will empower researchers to initiate inland Ciona cultures with low costs and reduced space constraints.